STUDI KASUS PENERAPAN PENDIDIKAN KESEHATAN TEKNIK MENYUSUI YANG BENAR UNTUK MENCAPAI KEBERHASILAN ASI EKSKLUSIF (Jurnal Kesehatan Siliwangi, 2021)
Breast milk has the most appropriate advantages for the growth and development of infants. WHO recommends breastfeeding in infants in the first hour after delivery and continued until the age of six months. The Indonesian Ministry of Health adopted a recommendation for exclusive breastfeeding until the baby is six months old. Lactation management is all efforts made to help achieve the success of exclusive breastfeeding. Correct breastfeeding technique is one of lactation management. The purpose of this case study is to find out the description of the provision of health education about the correct breastfeeding technique to achieve the success of exclusive breastfeeding. This case study uses a qualitative case study research approach to provide an overview of the application of correct breastfeeding technique health education to breastfeeding in multiparous postpartum mothers and supports the achievement of exclusive breastfeeding which will be carried out from April to June 2021. The respondents are Mrs. R is 27 years old, a postpartum mother who is still confused about the correct breastfeeding technique. The results of this case study using poster media and demonstration of correct breastfeeding techniques, Mrs. R is able to perform the correct breastfeeding technique, including the position of the mother and baby, the attachment of the baby's mouth, and how to burp the baby, so that there is an increase in knowledge of Mrs. R after the correct breastfeeding technique health education was carried out. Keywords: health education, breastfeeding technique, exclusive breastfeeding